Shipboard ADCP current measurements (38 kHz) during RV MARIA S. MERIAN cruise MSMX16 - Robert Kopte (PANGAEA, 2024)
Current velocities of the upper water column along the cruise track of R/V Maria S. Merian cruise MSMX16 were collected by a vessel-mounted 38 kHz RDI Ocean Surveyor ADCP. The ADCP transducer was located at 6.0 m below the water line. The instrument was operated in narrowband mode (WM10) with a bin size of 32.00 m, a blanking distance of 16.00 m, and a total of 50 bins, covering the depth range between 54.0 m and 1622.0 m. Heading, pitch and roll data from the ship extquotesingles motion reference unit and the navigation data from the Global Positioning systems were used by the data acquisition software VmDAS internally to convert ADCP velocities into earth coordinates. Single-ping data were screened for bottom signals and, where appropriate, a bottom mask was manually processed. The ship extquotesingles velocity was calculated from position fixes obtained by the Global Positioning System (GPS). Accuracy of the ADCP velocities mainly depends on the quality of the position fixes and the ship extquotesingles heading data. Further errors stem from a misalignment of the transducer with the ship extquotesingles centerline. Data post-processing included water track calibration of the misalignment angle (0.8116° +/- 0.7860°) and scale factor (0.9972 +/- 0.0184) of the Ocean Surveyor signal. The velocity data were averaged in time using an average interval of 60 s. Velocity quality flagging is based on different threshold criteria: Depth cells with ensemble-averaged percent-good values below 25% are marked as extquotesinglebad data extquotesingle. Depth cells with velocities above 1.5 m/s are flagged as extquotesinglebad data extquotesingle. Depth cells with a root-mean-square deviation between the measured ensemble-average velocity and a cell-wise running-mean velocity above 0.3 m/s are flagged as extquotesingleprobably bad data extquotesingle.